Extending the Curtin-Hammett principle: the relative rates of intramolecular cyclisation versus intermolecular processes - Henstridge, M; Davies, S; Thomson, J; Compton, R (2014)
A common tactic for synthetic chemists is to employ high dilution to ensure cyclisation is favoured over intermolecular processes. This intuitive strategy is ubiquitous in synthesis, although a quantitative analysis of these systems has not previously been proposed. In this Letter a theoretical analysis of the Curtin-Hammett principle when applied to systems in which the two equilibrating reactive species each undergo reactions of different orders is reported. This quantitative analysis predicts that a change in product distribution will be observed over time (under fixed conditions). However, the product ratios may be controlled by the addition of excess reagent(s) or by altering their concentration(s), consistent with established best practice (i.e., high dilution to maximise the formation of cyclised products, and high concentrations of reagents to maximise the formation of products resulting from intermolecular reactions). © 2014 Elsevier Ltd. All rights reserved.